Imported Intermediates, Absorptive Capacity and Productivity: Evidence from Ghanaian Manufacturing Firms - Okafor, L.; Bhattacharya, M.; Bloch, Harry (Wiley-Blackwell Publishing, 2017)
© 2016 John Wiley & Sons Ltd This paper analyses whether the use of imported intermediates improves productivity using firm-level panel data of manufacturing firms in Ghana covering the period between 1991 and 2002. This includes examining the importance of absorptive capacity (ABC) in enhancing the productivity gains from imported intermediates. We propose lagged relative productivity as a new measure of ABC. For any given period, ABC is defined as the natural logarithm of a firm’s total factor productivity (TFP) in the previous period relative to the firm’s initial TFP. An alternative measure of ABC considers real value added per worker in lieu of TFP. Overall, we find that firms with high levels of ABC derive productivity gains from the contemporaneous and prior use of imported intermediates, particularly for firms operating in the input-intensive industries. Our findings are robust to different specifications of the base model and different estimation techniques.